2017
DOI: 10.3847/1538-4357/aa91d1
|View full text |Cite
|
Sign up to set email alerts
|

Variational Estimation of the Large-scale Time-dependent Meridional Circulation in the Sun: Proofs of Concept with a Solar Mean Field Dynamo Model

Abstract: We present in this work the development of a solar data assimilation method based on an axisymmetric mean field dynamo model and magnetic surface data, our mid-term goal is to predict the solar quasi cyclic activity. Here we focus on the ability of our algorithm to constrain the deep meridional circulation of the Sun based on solar magnetic observations. To that end, we develop a variational data assimilation technique. Within a given assimilation window, the assimilation procedure minimizes the differences be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Under the assumption that meridional flow modulations are the main factor controlling the buildup of the poloidal field from AR sources, Hung et al (2015), Hung et al (2017) suggest an inverse approach to derive flow variations from magnetic data. As, however, we will see in the next subsection, the validity of the underlying assumption is open to question.…”
Section: Photospheric Flow Variationsmentioning
confidence: 99%
“…Under the assumption that meridional flow modulations are the main factor controlling the buildup of the poloidal field from AR sources, Hung et al (2015), Hung et al (2017) suggest an inverse approach to derive flow variations from magnetic data. As, however, we will see in the next subsection, the validity of the underlying assumption is open to question.…”
Section: Photospheric Flow Variationsmentioning
confidence: 99%
“…In recent years, dynamo models based on the Babcock-Leighton mechanism have been successful in explaining different observational aspects regarding solar activity (Dikpati & Charbonneau 1999;Nandy & Choudhuri 2002;Choudhuri et al 2004;Nandy et al 2011;Choudhuri & Karak 2012;Bhowmik & Nandy 2018;Hazra & Nandy 2019;Bhowmik 2019). Recently, data-driven 2.5D kinematic dynamo models and 3D kinematic solar dynamo models have also been developed to study different observational aspects regarding solar activity (Brun 2007;Jouve et al 2011;Yeates & Muñoz-Jaramillo 2013;Hung et al 2017;Hazra et al 2017;Karak & Miesch 2017;Hazra & Miesch 2018;Kumar et al 2019). For reviews of the solar and stellar dynamo model, see Charbonneau (2005), Brun et al (2015), and Brun & Browning (2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are some caveats in analyzing the raw results of our solar cycle 25 predictions. For instance, our current dynamo model does not yet include large asymmetries between rising and declining phases of the cycle nor a time derivative of the meridional circulation state (we assume constant flow for the time being but can perform time dependent inversions as demonstrated in (Hung et al 2017)). Further the Waldmeier effect is only captured by adapting the diffusivity profile at the base of the convection zone as done by (Karak & Choudhuri 2011).…”
Section: Discussion Of Our Predictions and Caveatsmentioning
confidence: 99%
“…Here, we focus on predicting solar cycle 25, using solar cycle 24 data (so-called "recent climatology"). An extensive description of Solar Predict can be found in (Jouve et al 2011;Hung et al 2015Hung et al , 2017 and an image summarizing the pipeline is shown in Figure 1.…”
Section: Brief Presentation Of the Solar Predict Data Assimilation Pimentioning
confidence: 99%